A Psycholinguistic Analysis of Speech Delay in Irish Bella’s Child - Maduri Saskya Maharani (Journal of Social, Culture, and Language, 2025)
The increasing prevalence of speech delay in early childhood has become a significant concern in the digital age, particularly with excessive screen time exposure. This study examines the case of Air Rumi, the first child of Indonesian acftress Irish Bella, who experienced speech delay attributed to environmental factors including gadget overuse and limited social interaction during the COVID-19 pandemic. Using a qualitative case study approach, this research applies psycholinguistic theories including Vygotsky’s Social Interactionist Theory, Krashen’s Input Hypothesis, and the Critical Period Hypothesis to analyze the contributing factors and intervention strategies. Data were collected from public interviews and social media content where Irish Bella discussed her child’s condition. The findings reveal that excessive screen time and reduced face-to-face interaction significantly impacted the child’s language development, while targeted interventions including speech therapy and increased parental interaction led to notable improvements. This study contributes to understanding how environmental factors influence language acquisition and emphasizes the importance of early intervention in speech delay cases.Keywords: Speech delay, Psycholinguistics, Language acquisition, Screen time, Social interaction